2021
DOI: 10.3390/rs13214475
|View full text |Cite
|
Sign up to set email alerts
|

Research and Analysis of Ecological Environment Quality in the Middle Reaches of the Yangtze River Basin between 2000 and 2019

Abstract: Ecological environment quality is a long-term continuous concept that is affected by various environmental factors. Its assessment has important implications for implementing the planning and protection of dynamic regional ecosystems. Therefore, this study attempted to obtain these indicators (green, dry, wet, heat) through the Google Earth Engine (GEE) platform, and then coupled the ecological environment quality index in the middle reaches of the Yangtze River Basin (MYRB) between 2000 and 2019, based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The slope of change and z-value significance level of the time series EQI can be visualized using Sen's slope and the Mann-Kendall test (Eq.-9), which can then be used to pinpoint the study area's significant EQI change areas (Table 3) (Tong et al, 2018;Jia et al, 2021;Zhang et al, 2021).…”
Section: Time Series Analysis Of Ecological Quality Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The slope of change and z-value significance level of the time series EQI can be visualized using Sen's slope and the Mann-Kendall test (Eq.-9), which can then be used to pinpoint the study area's significant EQI change areas (Table 3) (Tong et al, 2018;Jia et al, 2021;Zhang et al, 2021).…”
Section: Time Series Analysis Of Ecological Quality Changesmentioning
confidence: 99%
“…As an ecological parameter with continuous long-term characteristics, ecological quality is strongly influenced by various environmental factors (Zhang et al, 2021), and geospatial techniques can rapidly, accurately, and quantitatively assess the spatial and temporal changes in the ecoenvironment quality (Jia et al, 2021;Maity et al, 2022). The application of remote sensing technology has the advantages of rapid, efficient, and wide-area observation, and it can accurately record ecological conditions on the land surface, including land use/cover changes, surface temperature changes, and vegetation succession processes (Shan et al, 2019;Ermida et al, 2020;Szewczak et al, 2020;Firozjaei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the spectral information and morphological and other features in the images, we used the normalized difference water index (NDWI), the modified normalized difference water index (MNDWI), the maximum likelihood method and random forest to extract the edge information of the Yellow River water bodies. MNDWI and NDWI are ratio indexes that rely on the characteristics of river water in multispectral bands (such as the highest and lowest reflectance bands); the differences among land cover types are emphasised by the ratio, with the brightness of water bodies enhanced to their maximum value, while background features are suppressed in processed images [67,68]. The maximum likelihood method is important in supervised classification.…”
Section: Edge Information Extraction For the Yellow River At The Nort...mentioning
confidence: 99%
“…In addition, the development and utilization of water resources will also cause changes in land use types and ecological environment quality. Recently, the development of remote sensing technology has provided substantial data for ecosystem monitoring [5] . Different scholars discussed the land use change and ecological environment quality in different regions based on remote sensing ecological index, and found that human activities had a great impact on ecological environment [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%